INFLUENCE OF FLANGED-CUTOUT ON THE DYNAMIC BEHAVIORS OF A RECTANGULAR PLATE - WANG WenSheng; WANG Bin (Jixie qiangdu)
In practical engineering,punching cutouts on the structure results in forming flanging side simultaneously. This paper focus on the influence of flanged-cutout on the dynamic behaviors of a rectangular plate. The ANSYS software is used to evaluate the natural frequencies of the structure with different parameters of the flanged-cutout,such as size,flanging height and position. Numerical results show that the frequencies are highly dependent upon the parameters of the cutout,and the effect is related to the different boundary conditions of the plate. The results can provide references for the design of flanged-cutouts in engineering.